GEOGRAPHY, POLITICAL ECOLOGY AND TRANSFORMATIVE CHANGE IN THE 21ST CENTURY - Espinoza-Cisneros, Edgar (2025)
Since Geography's shift toward a normative focus in the seventies, Political Ecology has been a dynamic field seeking to understand the root causes of socio-environmental challenges while also proposing solutions. In this article, we reflect on the potential contribution of the geographical field of Political Ecology to the transformative change necessary to steer society towards sustainability in the 21st century in light of pressing challenges. We do this first by identifying three specific and overlapping axes of contribution of Political Ecology to transformative change based on the general thematic approaches of this field, and then by relating Political Ecology to recent conceptual-analytical frameworks on transformative change. Finally, we suggest some areas of improvement in Political Ecology to further strengthen the contribution to transformative change.